Interaction, Mechanism and Synergism of Rare Earth in [A336][DEHPA] Extraction System - Nurul Ain, Ismail; Anwaruddin, Hisyam; Safuan, Shariff; Badhrulhisham, Abdul Aziz (International Network for Scientific Information Publication (INSI), 2016)
The synergistic effect of rare earth (RE) in binary extractant system is predominantly determined by the nature and strength of the interaction between the two extractants. In order to correlate qualitatively the interaction in the absence/presence of RE element such as samarium, FT-IR spectra for di-(2-ethylhexyl) phosphate (DEHPA) and Aliquat 336 (A336) extractants toward their precursors have been analyzed. Changes in the functional group behavior in the spectra confirmed the presence of interaction between the RE and extractants and the echanism was revealed to be ion association. Enhancement in the distribution coefficient and synergistic effect in the binary extractant system compared to the individual extractant using solvent extraction technique towards La (III), Sm (III) and Y (III) were also observed. The highest distribution coefficient is 2.62 from the Y (III), and then followed by Sm (III) and La (III) with synergistic enhancement of 1.10 and 1.06, respectively. This work demonstrates an impeccable extractant candidate for an improved and environmental friendly RE separation in both laboratory and industrial application